Islamic Economic Strategies for Strengthening Food Security and Renewable Energy in the Face of Global Volatility - Helena Ramadhani Harahap; Mutia Ananda Rahma Damanik (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2026)
Global volatility characterized by climate change, geopolitical tensions, and economic uncertainties poses significant threats to food security and energy sustainability. Islamic economic principles offer unique frameworks for addressing these challenges through ethical finance, risk-sharing mechanisms, and sustainable development paradigms. Bank Sumut, as a regional development bank in North Sumatra, demonstrates both the potential and the challenges of integrating Islamic banking operations within conventional financial structures. The bank successfully fulfills core regional development banking functions, including government treasury management, MSME financing, and geographic financial inclusion, showing commercial viability and development orientation. However, evaluation from Islamic economic perspectives reveals gaps in the integration of Islamic banking principles, transparency mechanisms, technology adoption, and comprehensive alignment with Islamic values of justice, ethics, and sustainable development.The Islamic banking unit at Bank Sumut operates under a dual-window system, maintaining separate accounting, governance, and operational procedures from conventional banking activities. Primary Islamic products include murabaha financing (cost-plus sales, 65% of Islamic financing), musharakah (partnership financing, 15%), mudharabah (profit-sharing financing, 10%), ijarah (leasing, 8%), and qardh hasan (benevolent loans, 2%). Sharia compliance verification follows standard Indonesian practices, including annual Sharia audits, quarterly Sharia Supervisory Board reviews, and internal monitoring, but these mechanisms rely on periodic retrospective reviews rather than real-time verification. Customer awareness and preference for Islamic banking products remain limited, indicating the need for enhanced education initiatives to increase understanding and demand.Islamic financing instruments such as murabaha, salam, musharakah, and mudharabah demonstrate significant potential in mobilizing capital for both food security and renewable energy projects. Murabaha dominates agricultural input financing, providing smallholder farmers with seeds, fertilizers, and equipment through cost-plus arrangements. Salam contracts facilitate commodity financing by providing upfront payments for future crop delivery, addressing working capital constraints. Musharakah and mudharabah partnerships are applied to larger agricultural enterprises and renewable energy ventures, aligning bank incentives with business success. Takaful schemes, particularly agricultural weather-index products, provide risk mitigation and have been enhanced through blockchain-based smart contracts for automated claims processing.Green sukuk have emerged as primary financing vehicles for renewable energy infrastructure, mobilizing capital from both Islamic and conventional investors. Ijarah (leasing) structures facilitate distributed renewable energy adoption by converting high upfront costs into manageable periodic payments. Musharakah mutanaqisah (diminishing partnership) structures have been adapted for community renewable energy cooperatives, promoting local ownership, capacity building, and sustainable operations. Challenges remain in long-term investment horizons, electricity price regulation, limited secondary market liquidity, and regulatory standardization for green projects and Sharia compliance.Blockchain technology has been applied in Islamic finance to address transparency, efficiency, and Sharia compliance verification challenges. Platforms for trade finance, sukuk issuance, supply chain finance, and zakat distribution demonstrate practical applications, reducing document processing times, enhancing real-time monitoring, and automating compliance verification through smart contracts. Transparency is enhanced through immutable record-keeping and multi-party access, while smart contracts encode Sharia rules directly into transaction execution. Adoption challenges include infrastructure investment, regulatory uncertainty, limited technical expertise, and interoperability with legacy systems.In the Indonesian context, Bank Sumut demonstrates conventional banking effectiveness while facing challenges fully integrating Islamic economic principles. The Islamic banking unit represents less than 10% of total operations, limiting comprehensive alignment with Islamic economic objectives. Transparency mechanisms, while meeting regulatory requirements, lack technological sophistication such as blockchain for real-time verification and stakeholder visibility. FinTech and blockchain adoption are limited, and artificial intelligence or advanced analytics for operational efficiency and development impact measurement have not been implemented. Human capital gaps, dual operational complexity, and regulatory constraints further constrain Islamic banking expansion.Despite these challenges, opportunities exist to strengthen both regional development contributions and Islamic economic alignment. Strategic expansion of Islamic banking, blockchain technology implementation, human capital development, and integrated performance measurement incorporating Islamic economic indicators such as job creation, wealth distribution, and ethical business support can enhance outcomes. Lessons from other successful regional Islamic banks, such as Bank Aceh Syariah, highlight the value of comprehensive staff training, phased product and process conversion, community engagement, provincial government support, and partnerships with national Islamic finance institutions.For Bank Sumut management, recommendations include developing a five-year Islamic banking expansion strategy targeting 20–25% of total operations, piloting blockchain applications for specific use cases like government fund tracking, investing in human capital development, implementing enhanced development impact measurement systems, and strengthening customer education initiatives. For policymakers and regulators, supportive regulatory frameworks, technical assistance for blockchain implementation, capacity building, and incentive structures to encourage Islamic banking expansion are essential. For researchers and practitioners, the case highlights the need to rethink institutional strategy, culture, and capabilities to authentically integrate Islamic economic principles while fulfilling regional development mandates.Future research directions include quantitative studies assessing the economic impact of regional development banks’ Islamic banking operations, comparative research across multiple banks, stakeholder interviews and surveys, experimental pilot studies of blockchain applications, longitudinal tracking of Islamic banking evolution, and policy analyses on effective regulatory frameworks supporting Islamic finance and technology integration. While this study relies on publicly available documents and focuses on a single case, it provides valuable insights into the opportunities and challenges of aligning regional development banking with Islamic economic principles, particularly within technologically evolving and socially diverse contexts like Indonesia. Keywords: Islamic finance, blockchain technology, food security, renewable energy, Sharia compliance